Revisión de gremios alimenticios y dieta en primates del neotrópico (2021)
The ecological study of primates has been focused on diverse factors such as social interactions, competition, biodiversity, and their interaction with the environment like seed dispersion. An intrinsic characteristic of primates that allows us to approach all the factors mentioned above is their diet, for this reason primates have been categorized according to the resources they consume mostly and mainly in three food guilds: frugivores, folivores and insectivores. ¿But how much information these categories give us about the diet of primates? In this study we proposed to do a full review of the diet of neotropical primates, evaluate the criteria for determining these food niches and see how much of the variation in the diet of primates is explained. We worked with a total of 82 diet studies for the main neotropical primates genera (n=15), we took the category determined by the author of the study and compare it with an own category...